Comparing Multi-Age and Homogeneous Classrooms in EFL Context: A Systematic Literature Review - Lili Nandita Auliya; Agung Ginanjar Anjaniputra (Universitas Islam Negeri Palopo, 2026)
Multi-age classrooms are still few and far between in Indonesia where the national policy is based on age-homogenous grouping in which students of the same chronological age are instructed together. Whilst this may make teaching simpler in administrative, it can limit approaches to inclusive and personalized learning, particularly in an English as a Foreign Language (EFL) setting where many learners will be very different in terms of their level of proficiency and need. This systematic literature review investigates the unique features of multi-age classrooms as opposed to homogenous classrooms especially in the field of EFL. PRISMA was used to evaluate 13 journal articles published between 2020 and 2025 from total 123 records. Five key elements of multi-age classrooms are identified by the findings such as peer learning and interaction, learner autonomy, identity and inclusivity, instructional flexibility, and social-emotional development. The review concludes that multi-age classrooms promote richer language learning opportunities and personalized pedagogy. For educators, these characteristics highlight both advantages and difficulties, particularly in environments with limited resources or multilingualism. The pedagogical dynamics and impacts of teaching EFL to multi-age classrooms are highlighted in this review.